Estudio químico de Trixis michuacana var. longifolia (D. Don) C.E. Anderson - Herrera Sanabria, Luis Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
From the chemical study of essential oil (EO) of Trixis michuacana var. longifolia, its nature and chemical composition were determined; what's more; allowed to establish the chemotypes, of which it has three: germacrene, muurolene and caryophyllene, being mainly sesquiterpenes. This analysis represents the first report of the main components of the EO of the species, which is a relevant contribution to the chemistry of the genus Trixis. The chemical study of the apolar extracts and intermediate polarity of the aerial parts of the species Trixis michuacana var. longifolia, allowed the isolation and characterization of the secondary metabolites: sitosterol (23), stigmasterol (24), heptacosane (46), β-amyrin palmitate (68) and 4-hydroxy-3-methoxybenzaldehyde (69); being 23 and 24 the major metabolites in the hexane extract of stems. On the other hand, 46 and 68 are the main components of the dichloromethane extract of leaves and compound 69 of the dichloromethane extract of stems. Additionally, the chemical reactivity of phytosterols 23 and 24 was explored in a series of chemical reactions that led to obtaining the isomers of 5α-sitostan-3-ol (70,70a), 5α-sitostan-3-one (72) and finally to stigmastane thiosemicarbazone (76), the latter being a novel structure.

Del estudio químico del aceite esencial (AEs) de Trixis michuacana var. longifolia, se logró determinar su naturaleza y composición química; además; permitió establecer los quimiotipos, de los cuales, posee tres: germacreno, muuroleno y cariofileno, siendo principalmente sesquiterpenos. Este análisis representa el primer reporte de los principales componentes del AEs de la especie, lo cual es un aporte relevante a la química del género Trixis. El estudio químico de los extractos apolares y polaridad intermedia de las partes áreas de la especie Trixis michuacana var. longifolia, permitió el aislamiento y caracterización de los metabolitos secundarios: sitosterol (23), estigmasterol (24), heptacosano (46), palmitato de β- amirina (68) y 4-hidroxi-3-metoxibenzaldehído (69); siendo 23 y 24 los metabolitos mayoritarios en el extracto hexánico de tallos. Por su parte 46 y 68, son los componentes mayoritarios del extracto de diclorometano de hojas y el compuesto 69 del extracto de diclorometano de tallos.Adicionalmente, se exploró la reactividad química de los fitosteroles 23 y 24 en una serie de reacciones químicas que llevó a la obtención de los isómeros del 5α-sitostan-3-ol (70,70a), a la 5α-sitostan-3-ona (72) y finalmente a la tiosemicarbazona de estigmastano (76), siendo esta última una estructura novedosa.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2021-1563; Aceites esenciales; Fitosteroles; Terpenos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6525